Knowledge based bioinformatics from analysis to interpretation - Alterovitz, Gil.; Ramoni, Marco F. (Chichester, West Sussex John Wiley & Sons, 2010)
"In order to deal with issues that arise from the current increase of biological data in genomic and proteomic research and present it effectively to a wider audience, broader coverage of recent developments in the field of knowledge-based systems and their applications is required. Most current texts are either outdated or do not include all the aspects in knowledge and data-driven representation, integration, analysis, and interpretation. This collection aims to address this issue by providing comprehensive coverage of knowledge driven approaches to bioinformatics"--Provided by publisher.
(Publisher-supplied data) Chapter 1 Knowledge Based Bioinformatics Eric Karl Neumann Chapter 2 Knowledge-Driven Approaches to Genome-Scale Analysis Hannah Tipney and Lawrence Hunter Chapter 3 Technologies and Best Practices for Building Bio-Ontologies Mikel Egaa Aranguren, Robert Stevens, Jesualdo Tom s Fern ndez Breis, Erick Antezana, Vladimir Mironov and Martin Kuiper Chapter 4 Design, Implementation and Updating of Knowledge Bases Sarah Hunter, Rolf Apweiler and Maria Jesus Martin Chapter 5 Classical Statistical Learning in Bioinformatics Mark Reimers Chapter 6 Bayesian Methods in Genomics and Proteomics Studies Ning Sun and Hongyu Zhao Chapter 7 Automatic Text Analysis for Bioinformatics Knowledge Discovery Dietrich Rebholz-Schuhmann, Jung-jae Kim Chapter 8 Fundamentals of Gene Ontology Functional Annotation Varsha K. Khodiyar, Emily C. Dimmer, Rachael P. Huntley and Ruth C.Lovering Chapter 9 Methods for Improving Genome Annotation Jonathan Mudge, Jennifer Harrow Chapter 10 Sequences from all Prokaryotic, Eukaryotic and Viral Genomes Currently Available could be Clustered According to Phylotype on a Large-scale Self-Organizing Map Constructed with High-Performance Supercomputers. Takashi Abe, Shigehiko Kanaya, Toshimichi Ikemura Chapter 11 Molecular Network Analysis and Applications Minlu Zhang, Jingyuan Deng, Chunsheng V. Fang, Xiao Zhang and Long J. Lu Chapter 12 Reactome and Integrative Pathway Knowledge bases Robin A. Haw, Marc Gillespie, ÿ Michael A. Caudy Chapter 13 Methods and Challenges of Identifying Bio-Molecular Relationships and Networks Associated with Complex Diseases/Phenotypes and their Application to Drug Treatments. Mie Rizig.
Electronic reproduction.
Keywords: Bioinformatics; Expert systems (Computer science)